91.4k views
8 votes
NAME
7. Factor each quadratic expression,

NAME 7. Factor each quadratic expression,-example-1
User Moberg
by
5.0k points

1 Answer

6 votes

Explanation:

x² - 2x - 35 = (x - 7)(x + 5).

x² + 3x - 54 = (x + 9)(x - 6).

x² - 4x + 4 = (x - 2)².

x² - 121 = (x + 11)(x - 11).

2x² + x - 15 = (2x - 5)(x + 3).

6x² - 7x - 24 = (3x - 8)(2x + 3).

3x² - 10x + 8 = (3x - 4)(x - 2).

10x² + 9x - 9 = (5x - 3)(2x + 3).

12x² + 25x + 12 = (4x + 3)(3x + 4).

15x² - x - 6 = (5x + 3)(3x - 2).

User Jon Rein
by
5.2k points